CHRISTIAN BURIAL GROUND IN THE VILLAGE OF KHUNZAKH (BASED ON THE MATERIALS OF THE DAGESTAN-GEORGIAN JOINT ARCHAEOLOGICAL EXPEDITION) - Gambasidze, Givi Gajozovic; Abiev, Askerhan Kamalovic (History, Archeology and Ethnography of the Caucasus, 2020)
The article introduces the materials of the archaeological excavations of the Dagestan-Georgian archaeological joint expedition on the identified Khunzakh burial ground in 1978-1979, located in the villages. Khunzakh, on the Khunzakh plateau (Republic of Dagestan). The hunzakh plateau is the Central part of the medieval state formations of Sarir and then the Avar Kingdom, which were the most important Christian centers of the Eastern Caucasus in the IX-XIII centuries.As a result of the work carried out, 11 burials were identified, Dating from the IX-XV centuries. All burials were covered with a cultural layer containing archaeological material of the XI-XIII centuries. The identified burials represent three types of funerary structures: 1) an elongated pit of sub-rectangular shape with rounded corners or elongated-oval shape; 2) elongated sub-rectangular pits, slightly tapering to the end North-Eastern wall (in the "legs"), with ledges-shoulders along the side longitudinal walls and with a sketch of their small stones above the pit; 3) elongated sub-rectangular pits, slightly tapering to the end North-Eastern wall (in the "legs"), with ledges-hangers around the perimeter of the pit. Ledges-hangers, obviously, were used for installation of overlappings from stone slabs or wooden planks. The funeral rite is generally monotonous and is characterized by the placement of corpses in elongated pits carved into the rock, with orientation along the Central axis along the line SVV-SWZ, with the position of the deceased stretched out on his back, head in the Western sector, more precisely on the SWZ, the absence of burial equipment. The main features of the funeral rite and Dating of the burial ground allow us to refer it to the number of early Christian monuments of Sarir and consider it as a monument reflecting the process of Christianization of the population of medieval Hunzakh.